The coral reef condition in cerocok beach waters of painan, West sumatera province - Khairil Ihsan; Elizal '; Thamrin ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research of coral reef was conducted in october 2013 in Tikus Island Waters ofBengkulu, Bengkulu Province. This research aim to analyse health of coral based on hardliving coral cover and its. The research used survey method by applying Line InterceptTrasect (LIT) which consisting of three main stations in depth 5 m.The type of coral reef in Tikus Island was fringging reef. Coral lifeform’s found inthe area were Acropora Branching (ACB), Acropora Digitate (ACD), Acropora Encrusting(ACE), Acropora Submassive (ACS), Acropora Tabulate (ACT) Coral Branching (CB), CoralMassive (CM), Coral Submassive (CS), Coral foliose (CF), Coral Encrusting (CE), and Coral MushRoom (CMR). The conditions of coral reef in the depth of 5 m was in good with 73,50percentage.Keywords : Tikus Island, Coral Reef, Acropore